The Instructional Effectiveness of Integrating Abstract and Realistic Visualization - Joseph, John H. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This study examined the question of whether the integration of abstract and realistic visualization can improve the effectiveness of visualized instruction. Two methods of integrating visualizations were investigated. The first method used hybrid illustrations, i.e., a real color photograph into which a line drawing segment has been inserted. This provided an abstract illustration of the important relevant elements to be communicated, as well as an arousing realistic context. The second method was through the simultaneous presentation of both a line drawing and a real color photograph. In this treatment the abstract line drawing could communicate the essential information and/or facilitate looking at the realistic illustrations. Subjects for the study were 490 tenth grade students enrolled in a mandatory health class. The instructional script dealt with the construction and operation of the heart and was accompanied by 37 visuals, designed to illustrate concepts and relationships for which visualization is likely to be beneficial. The results suggest that designers of visualized instruction may expect to enhance its effectiveness under general conditions by inclusion of realistic visualization. However, the inclusion of abstract visualization or the integration of abstract and realistic visualization should be based on such considerations as pacing, general ability, and the type of instructional objective. (Author/RAO)
ERIC Note: Paper presented at the Annual Convention of the Association for Educational Communications and Technology (New Orleans, Louisiana, March 1979); For related document, see IR 007 416.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Processes; Grade 10.; Illustrations; Media Research; Photographs; Pictorial Stimuli; Secondary Education; Speeches; Visual Aids; Visual Discrimination; Visual Perception; Visual Stimuli; Speeches/Meeting Papers; Reports, Research